Length-weight relationship and condition factor of Liza macrolepis (Smith) from polluted and unpolluted waters of Visakhapatnam - Sandhya, V; Shameem, U (Indian Journal of Fisheries, 2011)
Length-weight relationship was estimated for 730 fishes of Liza macrolepis, collected from unpolluted waters of Gosthani estuary (319) and polluted waters of Visakhapatnam Harbour (411). The results of the study indicated a high regression coefficient value (b) for mullets collected from unpolluted waters as compared to those from polluted waters, the regression equations being Log W = -17.551 + 3.6811 Log L (r = 0.7804) and Log W = -5.8171 + 2.0656 Log L (r = 0.80609) respectively. Studies on relative condition factor indicated higher mean Kn values in the fishes of unpolluted waters than of polluted waters. The present study indicates that the growth and condition of the fish is affected by the prevailing environmental conditions of the polluted waters